Effects of six priority controlled phthalate esters with long-term low-dose integrated exposure on male reproductive toxicity in rats. (March 2017) - Gao, Hai-Tao; Xu, Run; Cao, Wei-Xin; Qian, Liang-Liang; Wang, Min; Lu, Lingeng; Xu, Qian; Yu, Shu-Qin
Abstract: Human beings are inevitably exposed to ubiquitous phthalate esters (PEs) surroundings. The purposes of this study were to investigate the effects of long-term low-dose exposure to the mixture of six priority controlled phthalate esters (MIXPs): dimethyl phthalate (DMP), diethyl phthalate (DEP), di( n -butyl) phthalate (DBP), butyl benzyl phthalate (BBP), di(2-ethyhexyl) phthalate (DEHP) and di- n -octyl phthalate (DNOP), on male rat reproductive system and further to explore the underlying mechanisms of the reproductive toxicity. The male rats were orally exposed to either sodium carboxymethyl cellulose as controls or MIXPs at three different low-doses by gavage for 15 weeks. Testosterone and luteinizing hormone (LH) in serum were analyzed, and pathological examinations were performed for toxicity evaluation. Steroidogenic proteins (StAR, P450scc, CYP17A1 and 17β-HSD), cell cycle and apoptosis-related proteins (p53, Chk1, Cdc2, CDK6, Bcl-2 and Bax) were measured for mechanisms exploration. MIXPs with long-term low-dose exposure could cause male reproductive toxicity to the rats, including the decrease of both serum and testicular testosterone, and the constructional damage of testis. These effects were related to down-regulated steroidogenic proteins, arresting cell cycle progression and promoting apoptosis in rat testicular cells. The results indicate that MIXPs with long-term low-dose exposure may pose male reproductive toxicity in human. Graphical abstract: Highlights: The study fully reflects actual integrated exposure to phthalates with long-term low-dose model. Human actual PEs' exposure level adjusted with a safety factor was used as the medium exposure dose. Phthalates caused male reproductive toxicity with long-term exposure even below their TDI. The toxic effects of phthalates were associated with cell cycle, apoptosis and steroidogenesis.